Aqad Characteristics, Fund Flows and Market Structure in Performance: A Cross Sectional Analysis of International Islamic Funds - Ismail, A. G.; Kusairi, S. (Universiti Sains Islam Malaysia, 2024)
This research applies the multiple regression analysis to the cross-sectional data that cover 249 samples of international Islamic mutual funds from 1998 to 2007. The overall result suggests that aqad characteristics (Mudarabah, Murabahah and Musharakah) significantly influence fund performance. Musharakah aqad has the highest influence towards fund performance, and followed by Mudarabah than Murabahah aqad. The investors' reaction (fund flows as proxy) to market information has positive and significant influence towards fund performance, suggesting that the relationship between the fund flow and fund performance follows the "smart money" or performance flows hypothesis. Market structure of Islamic mutual fund has positive influence and significant performance that measured by Alpha using local index whether for Islamic or conventional capital market. This result suggests that the relationship between market structure and fund performance at local market follows the "structure conduct performance" hypothesis. The results of the interaction analysis also show that the effect of fund flows and market structure towards performance is different according to the categories of the characteristics aqad of International Islamic fund. Fund flows influence towards positive performance is the highest in Musyarakah aqad. However the influence of fund flow towards performance is not significant in Mudarabah aqad. Market structure has positive and highest influence towards performance in Musyarakah aqad. Fees and expenses as control variable have no influence towards fund performance.